Loss of p53 suppresses replication stress-induced DNA damage in ATRX-deficient neuroblastoma - Jesmin Akter (Nature Publishing Group, 2021)
Abstract Genetic aberrations are present in the ATRX gene in older high-risk neuroblastoma (NB) patients with very poor clinical outcomes. Its loss-of-function (LoF) facilitates the alternative lengthening of telomeres (ALT) pathway in tumor cells and is strongly linked to replication stress (RS) and DNA damage through G-quadruplex (G4) DNA secondary structures. However, limited information is available on ATRX alteration-related NB tumorigenesis. We herein knocked out (KO) ATRX in MYCN-amplified (NGP) and MYCN single copy (SK-N-AS) NB cells with wild-type (wt) and truncated TP53 at the C terminus, respectively, using CRISPR/Cas9 technologies. The loss of ATRX increased DNA damage and G4 formation related to RS in TP53 wt isogenic ATRX KO NGP cells, but not in SK-N-AS clones. A gene set enrichment analysis (GSEA) showed that the gene sets related to DNA double-strand break repair, negative cell cycle regulation, the G2M checkpoint, and p53 pathway activation were enriched in NGP clones. The accumulation of DNA damage activated the ATM/CHK2/p53 pathway, leading to cell cycle arrest in NGP clones. Interestingly, ATRX loss did not induce RS related to DNA damage response (DDR) in TP53-truncated SK-N-AS cells. p53 inactivation abrogated cell cycle arrest and reduced G4 accumulation in NGP clones. The loss of p53 also induced G4 DNA helicases or Fanconi anemia group D2 protein (FANCD2) with ATRX deficiency, suggesting that ATRX maintained genome integrity and p53 deficiency attenuated RS-induced DNA damage in NB cells featuring inactivated ATRX by regulating DNA repair mechanisms and replication fork stability.